The Effect of Tumour Growth on Immune Competence: A Study of DMBA Mammary Carcinogenesis in the Rat - Kearney, R. (Nature Publishing Group, 1970)
Circulating antibody response to flagella antigen has been measured in three groups of Sprague-Dawley rats after feeding with 7.12.DMBA in an attempt to differentiate carcinogen and tumour growth as causative agents in the depression of immune response seen in these animals. DMBA fed female rats developing tumours had progressive depression of both primary and secondary response as compared to control animals, and 7S and 19S antibody fractions were equally affected. Removal of tumours did not result in recovery of response. Attempts to prevent tumour development by mammectomy after DMBA feeding were unsuccessful, but the similar number of tumours found in this group was associated with an equal degree of antibody depression to that seen in the first experiment. Male animals fed DMBA did not develop malignant tumours, and showed no depression of immune response. Results suggest that tumour development plays a part in the depression of circulating antibody response seen in these animals, but that it is not directly related to the number of tumours, and is not reversible by tumour excision.